2003
DOI: 10.1097/00004647-200304000-00004
|View full text |Cite
|
Sign up to set email alerts
|

Regulation of Body Temperature and Neuroprotection by Endogenous Interleukin-6 in Cerebral Ischemia

Abstract: Although the function of fever is still unclear, it is now beyond doubt that body temperature influences the outcome of brain damage. An elevated body temperature is often found in stroke patients and denotes a bad prognosis. However, the pathophysiologic basis and treatment options of elevated body temperature after stroke are still unknown. Cerebral ischemia rapidly induced neuronal interleukin-6 (IL-6) expression in mice. In IL-6-deficient mice, body temperature was markedly decreased after middle cerebral … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
63
0

Year Published

2003
2003
2016
2016

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 78 publications
(65 citation statements)
references
References 56 publications
2
63
0
Order By: Relevance
“…However, the role of IL-6 in that phenomenon has been regarded as a doubleedged sword, since both neuroprotective and detrimental properties were associated to its expression. On one hand it has been shown that IL-6 protects cultured neurons (Carlson et al, 1999;Ali et al, 2000;Pizzi et al, 2004) and is beneficial in several models of neurodegenerative diseases (Bensadoun et al, 2001;Bolin et al, 2002;Penkowa et al, 2001;Loddick et al, 1998;Ali et al, 2000, Swartz et al, 2001Herrmann et al, 2003); on the other hand, chronic treatment of cultured neurons with IL-6 or chronic expression of IL-6 in astrocytes might result in neuronal death and neurodegeneration (Qiu et al, 1998;Nelson et al, 2004;Conroy et al, 2004;Campbell et al, 1993).…”
Section: Introductionmentioning
confidence: 99%
“…However, the role of IL-6 in that phenomenon has been regarded as a doubleedged sword, since both neuroprotective and detrimental properties were associated to its expression. On one hand it has been shown that IL-6 protects cultured neurons (Carlson et al, 1999;Ali et al, 2000;Pizzi et al, 2004) and is beneficial in several models of neurodegenerative diseases (Bensadoun et al, 2001;Bolin et al, 2002;Penkowa et al, 2001;Loddick et al, 1998;Ali et al, 2000, Swartz et al, 2001Herrmann et al, 2003); on the other hand, chronic treatment of cultured neurons with IL-6 or chronic expression of IL-6 in astrocytes might result in neuronal death and neurodegeneration (Qiu et al, 1998;Nelson et al, 2004;Conroy et al, 2004;Campbell et al, 1993).…”
Section: Introductionmentioning
confidence: 99%
“…In this regard, we had already shown that Stat3 phosphorylation is predominantly detected in surviving neurons after transient MCAO (Suzuki et al, 2001). In addition, IL-6 was proven to have neuroprotective effects against cerebral ischemia (Loddick et al, 1998;Herrmann et al, 2003). We recently found that the administration of anti-IL-6 receptor antibody to mice after MCAO enlarged the infarct size and aggravated the neurological deficits together with a significant reduction in Stat3 phosphorylation (Yamashita et al, submitted).…”
Section: Discussionmentioning
confidence: 99%
“…The procedure for infarct measurement on cryosections and correction for cerebral edema has been described previously (Herrmann et al, 2003). In a separate cohort of animals, the femoral artery was cannulated to measure arterial blood gases and mean arterial blood pressure.…”
Section: Methodsmentioning
confidence: 99%